Predictors for major adverse cardiovascular events among patients with acute coronary syndrome in Bosnia and Herzegovina - Namik Selimović; Amina Marić; Armin Šljivo; Aladin Altic; Irma Fajić; Lana Lekić; Azra Durak-Nalbantić (Medicinski glasnik, 2024)
Aim: Despite advancements in the diagnosis, treatment and monitoring of patients with acute coronary syndrome (ACS), morbidity and mortality following ACS remain high. The aim of this study was to actively seek possible predictors of adverse outcomes after ACS aiming to identify high-risk patients promptly. Methods: This retrospective cohort study investigated patients with ACS hospitalized at Clinical Centre of the University of Sarajevo from 2019 to 2021. Patients were followed up for a period of 12 months post-discharge to assess major cardiovascular events (MACE) and MACE associated independent predictors. Results: . The study included 121 patients, mostly male 102 (84.3%), with a mean age of 60.83±12.61 years; prevalent risk factors were hypertension 94 (77.7%), dyslipidaemia 84 (69.4%), diabetes mellitus 91 (75.2%), active smoking 67 (55.4%) and positive family history of cardiovascular diseases 81 (66.9%). MACE occurred in 33 (27.3%) patients since the initial ACS, and those patients were older (p=0.012), had higher level of creatinine (p<0.001), lower ejection fraction at discharge (p<0.001) and larger left atrial diameter (p=0.032). Serum creatinine (OR=1.014, 95% CI 1,003-1,026, p=0.017) and ejection fraction (OR=0.924, 95% CI 0,869-0,984, p=0.013) were independent predictors associated with a 12-month follow up MACE following ACS. Conclusion: A monitoring of serum creatinine level, left atrial diameter, and ejection fraction post-acute coronary syndrome as potential indicators of future MACE within a 12-month follow-up period is of great importance. These findings emphasize the need for tailored management strategies to mitigate risks in this patient population.
Keywords: cardiovascular dis-eases; creatinine; echocardiography; heart disease risk factors; myocardial infarction